Key Predictors of Medication Adherence Among Pulmonary Tuberculosis Patients: A Cross-Sectional Study in Palembang, Indonesia - Sarfika, Rika; Martini, Endang; Yuliharni, Siti; Saifudin, I Made Moh. Yanuar (Nurse Media Journal of Nursing, 2025)
Background: Medication adherence remains a critical challenge in tuberculosis (TB) control, particularly in Indonesia, which ranks second globally in TB incidence. While previous studies have examined adherence factors worldwide, limited research has simultaneously evaluated the combined influence of sociodemographic, clinical, and psychosocial determinants in Indonesian settings, particularly using validated Indonesian-language instruments.Purpose: This study aimed to identify and quantify key predictors of medication adherence among pulmonary TB patients in Palembang, Indonesia, with particular emphasis on sociodemographic factors, clinical variables, and psychosocial determinants.Methods: A cross-sectional analytical study was conducted involving 150 pulmonary TB patients recruited through consecutive sampling at five public healthcare centers in Palembang. Data were collected using validated instruments, including the 8-item Morisky Medication Adherence Scale (MMAS-8) for adherence, the Knowledge About Tuberculosis Questionnaire (KATUB-Q) for TB knowledge, a structured questionnaire for side effects, the Treatment Motivation Questionnaire, the Multidimensional Scale of Perceived Social Support (MSPSS), and the TB-related Stigma Scale. Statistical analyses included descriptive statistics, Chi-square tests, and ordinal logistic regression to evaluate relationships between variables and adherence levels.Results: Only 20% of participants demonstrated high adherence, while 50.7% exhibited low adherence. Significant predictors of adherence included early adulthood (OR = 0.061, 95% CI = 0.004–0.857, p = 0.038) and middle adulthood (OR = 0.052, 95% CI = 0.005–0.565, p = 0.015), indicating lower adherence compared to late elderly. Other predictors were poor TB knowledge (OR = 0.316, 95% CI = 0.154–0.650, p = 0.002), low motivation (OR = 0.244, 95% CI = 0.108–0.553, p < 0.001), limited family support (OR = 0.470, 95% CI = 0.232–0.952, p = 0.036), insufficient healthcare worker support (OR = 0.349, 95% CI = 0.204–0.840, p = 0.015), and the presence of drug side effects (OR = 5.294, 95% CI = 2.134–13.126, p < 0.001). Younger adults showed lower adherence rates compared to older populations, while patients with better knowledge and stronger support systems demonstrated higher adherence.Conclusion: Key predictors of medication adherence were age, TB knowledge, motivation, family support, healthcare worker support, and drug side effects. Younger patients, those with poor knowledge, low motivation, weak support systems, and severe side effects demonstrated significantly lower adherence rates. These findings highlight the need for targeted, multifactorial interventions to improve TB treatment outcomes in Indonesia.